Chapter The Coastal village of Zvërnec - Laurìa, Antonio (Studi e saggi, 2020)
Part III of the book focusses on Zvërnec, a small village located in the southern part of the Lagoon of Nartë, on a promontory over a small gulf (Gjiri i Vogël), which looks like a miniature of the 'great' Gulf of Vlorë (Gjiri i Vlorës). Zvërnec is part of the Protected Landscape Vjosë-Nartë and is well-known for the suggestive island which hosts the Byzantine church of the Dormition of Mary (Category I Cultural Monument), which every year attracts many faithful and tourists alike, both Albanian and foreign. In the first chapters, the importance of the intangible heritage is stressed. In Zvërnec the cultural traditions in the lagoon area play a pivotal role, especially the fishing tradition together with the culinary tradition connected to sea products. In the following chapters, the multiple aspects of the tangible heritage are analysed. The protected landscape of Vjosë-Nartë requested a special attention. It includes a number of habitats, which constitute one of the most significant assets in terms of biodiversity at a national level. Unfortunately, both active and dismantled industrial sites present in the area as well as questionable development policies, threaten the fragile and delicate lagoon landscape. As far as the built heritage is concerned, the Church of the Dormition of Mary, traditional dwellings and the abandoned military heritage were thoroughly analysed. For each of the aforementioned issues, the theoretical and historical analysis are closely bound to an evaluation of those features of the cultural heritage that could be enhanced to guarantee a sustainable tourism development of the area. Each chapter ends with a consistent set of specific intervention strategies. They are substantive tools for action aimed at public and private local actors.